Frontiers in health policy research. - Cutler, David M.; Garber, Alan M. (MIT Press, 2004)
This series from the NBER presents new research by leading economists on current health care policy issues. The papers in this seventh volume, originally presented at the annual Frontiers in Health Policy Research conference held in Washington D.C. in the summer of 2003, reflect the economic challenges faced by policymakers and health care professionals in an age of budget deficits. Topics discussed include prescription drug benefits as a stand-alone component of Medicare, disability rates and Medicare costs, and conversion to for-profit health plans.